2021
DOI: 10.1091/mbc.e20-11-0698
|View full text |Cite
|
Sign up to set email alerts
|

The LINC complex is required for endothelial cell adhesion and adaptation to shear stress and cyclic stretch

Abstract: The Linker of Nucleoskeleton and Cytoskeleton (LINC) complex is a structure consisting of nesprin, SUN, and lamin proteins. A principal function of the LINC complex is anchoring the nucleus to the actin, microtubule, and intermediate filament cytoskeletons. The LINC complex is present in nearly all cell types, including endothelial cells. Endothelial cells line the inner most surfaces of blood vessels, and are critical for blood vessel barrier function. In addition, endothelial cells have specialized functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…Disabling LINC complex function may affect cell fate via number of mechanisms. Our group and others have shown that both dnKASH expression 21,22 and Sun1/2 co-depletion 23,24 alters the force generation and dynamics of focal adhesions. In mesenchymal stem cells (MSC), both approaches impair the activation of signaling molecules FAK (Focal Adhesion Kinase) and Akt (Serine/Threonine Kinase) in response to mechanical vibrations, thus limiting the RhoA mediated increase in cell contractility 25 .…”
Section: Introductionmentioning
confidence: 72%
“…Disabling LINC complex function may affect cell fate via number of mechanisms. Our group and others have shown that both dnKASH expression 21,22 and Sun1/2 co-depletion 23,24 alters the force generation and dynamics of focal adhesions. In mesenchymal stem cells (MSC), both approaches impair the activation of signaling molecules FAK (Focal Adhesion Kinase) and Akt (Serine/Threonine Kinase) in response to mechanical vibrations, thus limiting the RhoA mediated increase in cell contractility 25 .…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, under static conditions, nesprin-1 and -2 knockdown resulted in increased actin stress fiber formation (King et al, 2014). More recently, experiments in endothelial cells expressing a dominant negative KASH construct (DN-KASH), which displaces all endogenous nesprins from binding to their cytoskeletal components demonstrated its importance in promoting endothelial celladhesion, barrier formation, and focal adhesions (Denis et al, 2021). In support of these results, Yang and colleagues observed a role of nesprin-1,-2 in expression of tight junction proteins ZO-1 and occludin (which bind actin and microtubules), under atheroprotective pulsatile flow (Yang et al, 2020).…”
Section: From the Cell Surface To The Nucleus: Roles Of The Cytoskeletonmentioning
confidence: 99%
“…These vimentin cages serve to maintain nuclear integrity in cells migrating across tight spaces and loss of vimentin resulted in DNA-damage following nuclear constriction (Patteson et al, 2019). In addition, DN-KASH expressing endothelial cells also display collapse of the vimentin network suggesting vimentin's close association with the nucleus in ECs likely plays a similar protective role (Denis et al, 2021). Studies on ECs in vitro using nesprin-3 knockdown surprisingly promoted an elongated cell phenotype under static culture conditions and an increase in centrosome to nucleus distance (Morgan et al, 2011).…”
Section: Intermediate Filament Vimentin and Nuclear Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, perturbation of the LINC complex using dominant-negative KASH (DN-KASH), which broadly interferes with nesprin-SUN interaction, causes impaired propagation of intracellular forces and disturbs the organization of the perinuclear actin and intermediate filament networks ( Lombardi et al, 2011 ). Endothelial cells expressing DN-KASH alter cell–cell adhesion, barrier function, cell–matrix adhesion, and FA dynamics ( Denis et al, 2021 ). In addition, nesprin-1 depletion in endothelial cells increases the number of FAs, cell traction force, and nuclear height ( Chancellor et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%